The effect of project-based blended learning (PJB2L) learning model on students learning outcomes - Distyasa, Mira Juwita Eva; Winanti, Elizabeth Titiek; Buditjahjanto, I G P Asto; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2021)
The main problem in education today is the lack of effectiveness in the learning process. This can be seen from the average student learning outcomes which are always still low. Especially for vocational high school students who emphasize learning skills in order to produce work-ready graduates, but it is inversely proportional to the facts in the field. Low learning outcomes are indicated because the learning conditions are still conventional (lectures, practicum, and discussions) where teachers are still a source of learning (teacher centered). This study aims to determine the effect of the project based blended learning model on learning outcomes of vocational high school students. This research was conducted through a literature review and relevant research results and was continued through a Focus Group Discussion (FGD). From the research it was found that there was a significant positive influence between the variable model of project based blended learning and student learning outcomes, which means that student learning outcomes can be improved through the application of a project based blended learning model.